Step-by-step explanation:
2x(squared)+9x+9=—1
2x(squared)+9x+9+1=0
2x(squared)+9x+10=0
multiply the coefficient of x and 10=2x10=20
2x(squared)+9x+10=0
look for two numbers that when added gives 9and when multiplied gives 20
2x(squared)+5x+4x+10=0
(2x(squared)+5x)+(4x+10)=0
find the number and letters that are common in the equations
x(2x+5)+2(2x+5)=0
(x+2) (2x+5)=0
x+2=0
collect like terms
x=0-2
x=-2
2x+5=0
collect like terms
2x=0-5
2x=-5
divide both sides by 2
2x/2=-5/2
x=-5/2
so x=-2 and -5/2
Answer:
27
Step-by-step explanation:
Answer:
-3(-3x + 4) = 9x - 12
Step-by-step explanation:
-3( Ax + 4) = 9x - 12
-3Ax -12 = 9x - 12
Equating coefficients of x terms on both sides :
-3A = 9
A = -3
Therefore, -3(-3x + 4) = 9x - 12
Answer:
11
Step-by-step explanation:
250+25= 275 is your answer